ESJF Algorithm to Improve Cloud Environment: Cloud computing - Younis, Manal F. (Iraqi Journal of Science, 2021)
Nowadays, after the technological development in societies, cloud computing has become one of the most important technologies. It provides users with software, hardware, and platform as remote services over the Internet. The increasing number of cloud users has caused a critical problem in how the clients receive cloud services when the cloud is in a state of instability, as it cannot provide required services and, thus, a delay occurs. Therefore, an algorithm was proposed to provide high efficiency and stability to work, because all existing tasks must operate without delay. The proposed system is an enhancement shortest job first algorithm (ESJF) using a time slice, which works by taking a task in the shortest time first and then the longest first from the queue. Through the experimental results in decreasing the waiting and completion time of the task, as well as taking into account reducing tasks starvation, the result of the proposed ESJF algorithm was compared with the traditional shortest job first (SJF) algorithm. These algorithms were applied when all tasks arrived at the same time, and it proved that the ESJF algorithm works more efficiently compared to SJF.